DIGITALISATION OF MSMES – AN ANALYSIS (International Journal of Management (IJM), 2024)
Aim: This insight paper's objective is to give a general overview of digitalization in Indian MSME sector. Micro, small, and medium-sized businesses (MSMEs) in India have experienced numerous breakthroughs in the past few years, such as the implementation of the GST system and escalating global rivalry. These difficulties also offer a chance to embrace digital technology in order to get over challenging circumstances. MSMEs' innate capacity for growth and their use of digital business practices will undoubtedly aid the industry in reaching its full potential. The MSME sector has historically been one of the main engines of the Indian economy. As a key component of this renaissance, digitalization is improving manufacturing efficiency, resulting in higher-quality products, and assisting in the development of creative and original business models. The foundation of emerging countries like India are Micro small and medium-sized enterprises (MSMEs), which provide millions of families with work and a means of subsistence. In a nation with a sizable labour pool and a large demographic sector, MSMEs are essential to the expansion and growth of the economy. By 2028, the MSME sector in India is estimated to add $1 trillion to the nation's exports, accounting for about 33% of India's GDP. (pib.gov.in). There are 7.9 million small and medium-sized businesses (MSMEs) registered in India. There are 7.9 million small and medium-sized businesses (MSMEs) registered in India. These figures demonstrate the overall economic influence that this nation's mid-sized enterprises have. Thus, the authors' goal is to investigate the impacts and challenges of digitalization in the MSME sector and additionally recommend appropriate corrective actions for improved MSMEs' digitalization Research Methodology: The study analysis is qualitative in nature. The information was gathered from a number of publications, reports from the Indian government, published research articles, the MSME annual report, and other pertinent organizations and websites. The findings contain a conclusion and a list of suggestions.